Looking at ins and outs: a process documentation research on education for indigenous children programme - Kabir, Md. Mahbubul; Nath, Samir Ranjan; Zaman, Shahaduz (BRAC Research and Evaluation Division (RED), 2019)
Looking at Ins and Outs is a process documentation study on BRAC's Education for Indigenous Children (EIC) programme. BRAC's EIC programme was designed with a view to ensuring the general provision of education for indigenous children. Since out-set in 2002, it has been receiving enthusiasm from many stakeholders and non-stakeholders. When a planned extension of this programme was undertaken, a Process Documentation Research (PDR), a unique way of monitoring and assessing development work, seemed very useful. In this study, the different stages up to school opening process had been documented. Following were the stages consider for the study: 1) Staff foundation training, 2) School inaugural workshop, 3) School opening session, 4) Material development. Though there are many pros and cons, we found EIC programme striving to make an indigenous child friendly schooling system. Targeted community people seemed co-operative and optimistic. To ensure a compressive inclusion of the indigenous children in primary education and to give a break through in overall development of indigenous people, EIC programme requires many pragmatic supports from different stakeholders. PDR team, as a close stakeholder, was committed to give knowledge support through documentation. PDR findings would be justified if it could make some contribution on the planning and successful implementation of the programme.